Global Mpox transmission and stigma: addressing barriers in affected communities - Majani Edward; Odongo shadrack; Stephen Tetteh Engmann; Alfred Jubilate (Discover Public Health)
Abstract The ongoing mpox outbreak, characterized by the ongoing global circulation of clade II mpox since 2022, has disproportionately impacted marginalized communities and underscores the importance of addressing both the epidemiological aspects and the societal impact of the disease on affected communities. This article examines mpox transmission dynamics globally, with a focus on populations whose proactive health-seeking behaviors have enabled early identification of cases. Yet, these communities also face stigma rooted in homophobia, racism, and misinformation, which hampers healthcare access and fuels discrimination. This stigma results in delayed care-seeking and barriers to effective public health interventions. The article advocates for continuous monitoring, adaptive public health strategies, and anti-stigma efforts to ensure that affected populations receive the support they need. While mpox primarily spreads through close contact, including sexual contact, the article highlights regional differences in framing and addresses misconceptions.